MAKNA KOSAKATA “JATUH” DALAM BAHASA SUNDA DAN BAHASA JAWA - Emma Maemunah (Balai Bahasa Provinsi Bali, 2017)
Sundanese and Javanese language derived from the same proto language. There are many similarities in both languages. The similarities are in the form and meaning. This study discusses the form and the meaning of vocabularyof